Pengaruh Kualitas Pelayanan Pengurusan E-KTP terhadap Kepuasan Masyarakat Kecamatan Candi Sidoarjo - Aulia Septiana; Ertien Rining Nawangsari (Mahesa Research Center, 2022)
This article aims to determine the effect of five dimensions of service quality for making electronic ID Card, which consists of reliability, responsiveness, assurance, empathy, and physical evidence partially and simultaneously on community satisfaction at the Candi Sub District, Sidoarjo Regency. Problems is focused in the five main indicators that affect the quality of service such as reliability, responsiveness, assurance, empathy, and tangible. If the services provided have the following characteristics, it can be stated that the needs have been met which causes residents who use public services to get satisfaction. To approach this problem, it is used as a theoretical reference from Tjiptono, 2016 which states that there are five main indicators that have an influence on service quality. The data were collected through questionnaires distributed to 72 respondents who visited the Candi Sub District Office and analyzed quantitatively. This study concludes that there is a positive and significant partial and simultaneous influence of the five dimensions of service quality on community satisfaction at the Candi Sub District Office, Sidoarjo during the Covid-19 pandemic.